ANALISIS FRAMING BERITA PEMBUNUHAN DALAM ASAHI SHINBUN DAN YOMIURI SHINBUN - Wahyu Setiorini (Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. General focus of this research is the difference of murder news framing between Asahi Shinbun and Yomiuri Shinbun daily news. Especially, it will analyze framing through: (a) diction (symbol) and emphasis or reality minimalization in title, preliminary and news body; (b) motif being background of incident framing of both newspapers. Research data about news of murder to a woman contained in Asahi Shinbun and Yomiuri Shinbun daily news are studied with framing analysis as one of Critical Discourse Analysis. Foundings of the research are: Asahi fades murder suspect and as if it blames victims, while Yomiuri expresses fact of suspicious persons doing the murder and takes side with victims. Asahi takes firm on objectivity in positivism tradition and descriptive linguistic, while Yomiuri keeps participatory ethic which takes side with victims, subalternans and weak as well as weakened groups by unfair social structure, especially in a capitalistic society. Kata Kunci: analisis framing, minimalisasi, pembingkaian peristiwa, critical discourse analysis, participatory ethic